Faktor Penentu Efisiensi Investasi: Pelaporan Keuangan, Konservatisme Akuntansi, dan Jatuh Tempo Utang - Syifa Lathifunnisa; Dyarini Dyarini (Jurnal Proaksi, 2025)
Main Purpose - This study aims to examine the influence of financial reporting quality, accounting conservatism, and debt maturity on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange.Method - A quantitative approach was employed to analyze secondary data from 20 companies selected through purposive sampling, resulting in 100 observations. SPSS version 25 was used as the data analysis tool for regression analysis.Main Findings - The phenomenon of investment efficiency has become increasingly crucial following a 16.32% annual decline in manufacturing investment from 2017 to 2019. Market uncertainty and limited incentives hinder economic growth, making fund optimization essential to support this sector. The research findings reveal that the quality of annual financial reports, accounting conservatism, and debt maturity have a significant impact on investment efficiency.Theory and Practical Implications - These findings highlight the importance of financial reporting quality, accounting conservatism, and debt maturity structure in enhancing investment efficiency. They suggest that companies should manage these three aspects optimally to support better investment decision-making.Novelty - This study utilizes the latest data (2019–2023) and a larger sample, enabling a more comprehensive analysis of the dynamics, challenges, and opportunities in the manufacturing industry.